Changes in Caregiver Knowledge and Perceived Competency Following Group Education about Sensory Processing Disturbances: An Exploratory Study. (4th July 2016) - Gee, Bryan M.; Peterson, Theodore W.
Abstract: Parents or teachers ( n  = 10) of children diagnosed on the autism spectrum and exhibiting sensory processing disorders (SPD) attended a series of six weekly educational sessions designed to increase the participants' knowledge of SPD, skills in interacting with children exhibiting SPD and confidence in intervening with children exhibiting undesirable behaviours stemming from SPD. The sessions consisted of group classroom instruction with instructional methods including PowerPoint‐assisted lecture/discussion and short video clips. Pre‐test and post‐test assessment was made of the participants' (a) self‐perceived knowledge of sensory processing concepts; (b) actual knowledge of sensory processing concepts; and (c) self‐rated competency for dealing with children exhibiting behaviours related to SPD. Statistical analysis revealed significant gains were achieved on all measures. The results were interpreted as indicating that group classroom instruction is an effective means of increasing such caregivers' self‐perceived knowledge of sensory processing concepts, actual knowledge of sensory processing concepts and self‐rated competency for dealing with children exhibiting behaviours related to SPD. Future research to assess the short‐term and long‐term impacts of these gains and to gauge the relative effectiveness of various contents for such sessions is recommended. Copyright © 2016 John Wiley & Sons, Ltd.